Perancangan dan Implementasi Website sebagai Media Pemasaran Digital untuk UMKM Warkop Harapan Jaya - Hariefan Saputra; Muhammad Yahya; Sularno Sularno (CV. ITTC INDONESIA, 2025)
Warkop Harapan Jaya, a small and medium sized business specializing in coffee and snacks, has been operating for two years. Despite its loyal customers, the business faces challenges in reaching a wider market, particularly among younger, more digitally active customers. This project aimed to design and implement a simple, informative, and responsive website to increase online visibility, provide clear information to customers, and build a more modern brand image. The method used was a static website development approach with WEBFLOW. The project resulted in a fully functional website featuring a menu, gallery, location, and contact information. Initial impacts showed an increase in inquiries via WhatsApp and increased brand awareness among new visitors. It was concluded that website development was an effective and cost-effective strategic step for the MSME's digital transformation